Marcus Musurus and the Aldine Septuagint. With a reconsideration of the recently-recovered BH UCM 22 (442 Rahlfs) - Martins de Jesus, Carlos Alberto (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2024)
The following pages perform an evaluation of Marcus Musurus’ partial review of 1-2 Kings in two manuscripts (London, British Library, add 10968 [L] and Madrid, BH MS. 22 [M]). On the one hand, the nature and contexts of both codices reviewed by Musurus (the books he worked upon) provide valuable information on the long-debated issue of Aldus’ (and particularly Musurus’) access to Bessarion’s former Greek library, as it also stresses the need to reconsider the contexts of copying and revision of these codices. Especially M, which production, revision, and sending to Spain will be reconsidered. On the other hand, textual collation will confirm the use of several manuscript sources as part of Musurus’ well-known and praised philological work (the books he worked with), making the very revision of M, finally recovered, a part of the editorial process of the Aldine Septuagint.